NIR Photothermal‐Responsive Shape Memory Polyurethane with Protein‐Inspired Aggregated Chymotrypsin‐Sensitive Degradable Domains. Issue 21 (29th July 2022) - Yang, Ruibo; Liu, Wenkai; Song, Nijia; Li, Xin; Li, Zhen; Luo, Feng; Li, Jiehua; Tan, Hong
Abstract: Biodegradable shape memory polymers are promising biomaterials for stents used in minimally invasive surgical procedures such as intestinal stents. Herein, a series of biodegradable shape memory polyurethanes (SMPUs) containing a novel phenylalanine‐derived chain extender (PHP) are synthesized. Inspired by the fact that the function of biomacromolecules such as proteins is rich and varied because of the multiple combinations of the amino acid in highly evolved biosystems, this study finds that the sequence distribution of PHP in SMPU will also have a great influence on the phase structure and degradation behavior, especially the difference of surface morphology caused by degradation. Considering that the transition temperature ( T trans ) of SMPU obtained is higher than physiological temperature, oxidized carbon black (OCB) with the ability of photothermal conversion is introduced into SMPU, which can not only endow SMPU with near‐infrared response shape recovery characteristics, but also enhance phase separation degree and mechanical properties of them. SMPU/OCB composites show excellent shape memory effect and rapid photothermal response, and they can be degraded by chymotrypsin with an adjustable degradation rate. These SMPU/OCB composites show broad potential for application as intestinal stents. Abstract : In this work, biodegradable shape memory polyurethanes (SMPUs) containing different aggregation states of novel phenylalanine‐derived chain extender (PHP) domains and different content of oxidized carbon black (OCB) are synthesized. The sequence distribution of PHP in SMPU has great influence on phase structure and degradation rate, especially the surface morphology caused by degradation. These photothermal‐response SMPU/OCB composites show broad potential for self‐expanding intestinal stents.